2017
DOI: 10.3390/info8020065
|View full text |Cite
|
Sign up to set email alerts
|

Security Policy Scheme for an Efficient Security Architecture in Software-Defined Networking

Abstract: Abstract:In order to build an efficient security architecture, previous studies have attempted to understand complex system architectures and message flows to detect various attack packets. However, the existing hardware-based single security architecture cannot efficiently handle a complex system structure. To solve this problem, we propose a software-defined networking (SDN) policy-based scheme for an efficient security architecture. The proposed scheme considers four policy functions: separating, chaining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Overall, various survey-based studies highlighting the vulnerabilities in LPWAN communication technologies have identified an urgent need for secure and uninterrupted communication between an end-device and the gateway for secure and effective IoT networks for large-scale IoT deployments. While there is greater potential in the emergence of software-defined network (SDN) architecture for security in IoT, the protocols in SDN are still under development [37,38].…”
Section: Related Work and Research Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, various survey-based studies highlighting the vulnerabilities in LPWAN communication technologies have identified an urgent need for secure and uninterrupted communication between an end-device and the gateway for secure and effective IoT networks for large-scale IoT deployments. While there is greater potential in the emergence of software-defined network (SDN) architecture for security in IoT, the protocols in SDN are still under development [37,38].…”
Section: Related Work and Research Contributionmentioning
confidence: 99%
“…However, in such a heterogeneous operating environment, the IoT network with constrained resources is faced with significant security and privacy challenges. IoT devices with highly primitive security features are susceptible to attacks as they become entry points to infiltrate into critical infrastructures via the connected networks [38,41]. There is an escalation of new IoT threats and security risks, due to the inherent vulnerabilities in each of the four basic layers of the IoT architecture: In this section, we identify the potential risks and the key security requirements in each IoT layer from reported studies to form the key security requirements for our research problem [29,42,66,67].…”
Section: Security Requirements Of Iot Architecturementioning
confidence: 99%
“…Also, in a similar way to our proposal, SDN controllers have been used for security policy enforcement in specific scenarios [ 32 ] and for the detection of attacks such as DDoS (distributed denial of service) [ 33 ] and others [ 34 ] in that kind of network. There are also proposals for more generic intrusion detection and prevention systems for SDN-based networks [ 35 ], and the definition of security policies through these technologies has been also explored in works such as [ 36 ] or [ 37 ]. Although the use of SDN technologies is a very promising field in security, it requires the deployment of SDN-enabled devices in organizations’ networks and the modification of the current network management, which might have a high impact in terms of network reorganization and cost.…”
Section: Related Workmentioning
confidence: 99%